Renal expression of Hsp27, 60, and 70 in cases of fatal hypothermia. (March 2022) - Wegner, A.; Ulbricht, J.; Madea, B.; Doberentz, E.
Highlights: In case of a fast drop of the core body temperature, morphological findings of fatal hypothermia can be missing. Persistant vital thermal influences and tissue hypoxia are major factors that cause cellular stress. Hsps are expressed in case of cell stress to prevent aggregation of newly folded proteins and to stabilise cell structures. Our study could not confirm that Hsps can be used as a micromorphological marker for fatal hypothermia. Histological and immunochemical investigation of cases of fatal hypothermia must be continued. Abstract: Macromorphological findings can be missing in cases of fatal hypothermia when the agonal period is very short because of a large difference between environmental and core body temperatures. Expression of heat shock proteins (Hsps) increases under endogenous and exogenous cellular stresses such as thermal stress. These stress proteins can be revealed by immunohistochemical staining. Forty-five cases of death due to hypothermia and a control group of 100 deaths without any antemortem thermal stress were examined for Hsp27, 60, and 70 expression in renal tissue because renal tissue is sensitive to cellular stress. The results revealed no significant difference between Hsp27, 60, and 70 expression in both groups (28.8% positive staining in the study group and 19.0% positive staining in the control group), which is contradictory to a previous study on expression of Hsp70 in renal tissue in cases of fatal hypothermia. Hence, it is currently unclear whether immunohistochemical staining of Hsps supports a morphological diagnosis of fatal hypothermia.